Chemically strengthened glass and cover glass

Through chemical reinforcement treatment of specific distribution of Na and Si in the glass, the problem of insufficient drop strength of the cover glass is solved, and the high drop strength and impact resistance of the cover glass are achieved.

CN119143386APending Publication Date: 2024-12-17AGC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410751799.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-14
Filing Date
2024-06-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing cover glass is insufficient when falling, and it is prone to break due to deformation, making it difficult to remain intact when falling from a high position.

Method used

Chemical strengthening treatment is carried out by distributing Na and Si in glass to ensure that the Na/Si detection intensity ratio reaches excellent compression stress distribution within a specific depth range. The electron probe microscope analyzer is used to analyze and meet specific Na and Si distribution relationship to improve the drop strength of glass.

Benefits of technology

The drop strength of the cover glass has been significantly improved, and even if it falls from a higher position, it can avoid rupture, which improves the resistance to impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided is a chemically strengthened glass having excellent drop strength. The chemically strengthened glass is a plate-shaped chemically strengthened glass, and the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass as determined by an electron probe microanalyzer satisfy the relationship represented by formula (I). In formula (I): RNa / Si - 100-RNa / Si - C > = 0.055, RNa / Si - 100 is the average value of the Na / Si detected strength ratio, which is the ratio of the detected strength of the Na distribution to the detected strength of the Si distribution, within a depth range of 91-110 [mu] m from one surface of the chemically strengthened glass when the distance in the sheet thickness direction of the chemically strengthened glass is defined as depth. In formula (I), RNa / Si - C is the average value of the Na / Si detected strength ratio within a depth of + / -25 [mu] m from the center position of the chemically strengthened glass in the sheet thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemically strengthened glass. In addition, the present invention relates to a cover glass comprising chemically strengthened glass. Background Art

[0002] In recent years, cover glasses have been used to protect display devices such as mobile phones, smart phones, and tablet terminals and to improve their appearance. Cover glasses for these purposes are required to have excellent strength in order to prevent breakage due to impact or the like.

[0003] It has been known that glass is immersed in potassium nitrate molten salt and the like for chemical strengthening treatment to improve the surface strength of glass. For example, Patent Document 1 discloses that the surface strength of a glass plate is improved by immersing glass in potassium nitrate molten salt for chemical strengthening treatment. More specifically, it is disclosed that the strength of a glass plate is improved by sequentially subjecting glass containing Li to chemical strengthening treatment using a molten salt containing Na and a molten salt containing K. In addition, it is described that the mechanism for strengthening the strength of a glass plate by such chemical treatment is based on the compressive stress generated by the exchange of alkali metals.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-027424 Summary of the invention

[0007] In recent years, there is a demand for further improvement in the strength of the cover glass. The cover glass of a mobile terminal or the like may break due to deformation when dropped, and it is required that the cover glass does not break even when dropped from a higher position (has higher drop strength).

[0008] The present inventors have studied the cover glass described in Patent Document 1 and found that there is room for improvement in drop resistance.

[0009] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide chemically strengthened glass having excellent drop strength.

[0010] Another object of the present invention is to provide a cover glass.

[0011] The present inventors have conducted intensive studies on the above-mentioned problems and, as a result, have found that higher drop strength can be obtained by setting the distribution of Na in the plate thickness direction to a specific state, thereby completing the present invention.

[0012] That is, the present inventors have found that the above-mentioned problems can be solved by the following configuration.

[0013] [1] A chemically strengthened glass, which is a plate-shaped chemically strengthened glass,

[0014] The Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (I).

[0015] Formula (I) R Na / Si_100 -R Na / Si_C ≥0.055

[0016] In formula (I), R Na / Si_100 It is an average value of the Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution within a range of 91 to 110 μm from one surface of the chemically strengthened glass, when the distance in the thickness direction of the chemically strengthened glass is defined as the depth.

[0017] In formula (I), R Na / Si_C It is an average value of the Na / Si detection intensity ratio within a range of depth ±25 μm from the center position of the plate thickness of the chemically strengthened glass.

[0018] [2] The chemically strengthened glass according to [1], further satisfying the relationship of the following formula (II).

[0019] Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110

[0020] In formula (II), R Na / Si_50 It is an average value of the Na / Si detection intensity ratio within a range of 41 to 60 μm in depth from the surface.

[0021] [3] The chemically strengthened glass according to [1] or [2], further satisfying the relationship of the following formula (III).

[0022] Formula (III) R Na / Si_100_0 -R Na / Si_C ≥0.155

[0023] In formula (III), R Na / Si_100_0 In the distribution of the Na / Si detection intensity ratio, a first regression line is drawn from a range of 91 to 110 μm in depth from the surface, and the value of the Na / Si detection intensity ratio at the surface is determined based on the first regression line.

[0024] [4] The chemically strengthened glass according to any one of [1] to [3], wherein the K distribution and Si distribution in the thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (VI).

[0025] Formula (VI) R K / Si_2_0≤0.310

[0026] In formula (VI), R K / Si_2_0 In the distribution of the ratio of the detection intensity of the above-mentioned K distribution to the detection intensity of the above-mentioned Si distribution, that is, the K / Si detection intensity ratio, a second regression line is made from the range of 1 to 3 μm at a depth from the above-mentioned surface, and the value of the above-mentioned K / Si detection intensity ratio at the position of the above-mentioned surface is calculated based on the above-mentioned second regression line.

[0027] In formula (VI), R K / Si_C It is an average value of the K / Si detection intensity ratio within a range of depth ±25 μm from the center position of the plate thickness of the chemically strengthened glass.

[0028] [5] The chemically strengthened glass according to any one of [1] to [4], wherein the composition at the center of the plate thickness is expressed in terms of molar percentage based on oxides and comprises 55 to 75% SiO2, 8 to 20% Al2O3, 3 to 15% Li2O, 1 to 5% Na2O, 0 to 3% K2O, 0 to 10% MgO, 0 to 3% Y2O3, 0 to 3% ZrO2, 0 to 10% CaO, 0 to 5% SrO, 0 to 5% ZnO, 0 to 3% TiO2, 0 to 1% SnO2, 0 to 5% P2O5, and 0 to 10% B2O3,

[0029] The ratio of the content of ZrO2 to the total content of Y2O3 and ZrO2 is 0.0 to 0.7.

[0030] The total content of Y2O3 and the content of ZrO2 is greater than 0.0% and is less than or equal to 3.0%.

[0031] [6] The chemically strengthened glass according to any one of [1] to [5], wherein, in the composition at the center of the plate thickness, the ratio of the content of K2O to the content of Na2O is 0.0 to 1.8.

[0032] [7] The chemically strengthened glass according to any one of [1] to [6], wherein the value of the composition at the center of the plate thickness represented by [Al2O3]-[Na2O]-[K2O]+[Li2O] is 15.0 to 26.0.

[0033] Here, [Al2O3], [Na2O], [K2O] and [Li2O] respectively represent the contents of Al2O3, Na2O, K2O and Li2O in molar percentage based on oxides.

[0034] [8] A chemically strengthened glass, which is a plate-shaped chemically strengthened glass,

[0035] The Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (II).

[0036] Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110

[0037] In formula (II), R Na / Si_50 It is an average value of the Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution within a range of 41 to 60 μm from one surface of the chemically strengthened glass, when the distance in the thickness direction of the chemically strengthened glass is defined as the depth.

[0038] In formula (II), R Na / Si_C It is an average value of the Na / Si detection intensity ratio within a range of depth ±25 μm from the center position of the plate thickness of the chemically strengthened glass.

[0039] [9] A chemically strengthened glass, which is a plate-shaped chemically strengthened glass,

[0040] The Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron beam microanalyzer satisfy the relationship of the following formula (III).

[0041] Formula (III) R Na / Si_100_0 -R Na / Si_C ≥0.155

[0042] In formula (III), R Na / Si_100_0 When the distance in the thickness direction of the chemically strengthened glass is defined as the depth, in the distribution of the ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution, that is, the Na / Si detection intensity ratio, a first regression line is prepared from a range of 91 to 110 μm at a depth from the surface, and the value of the Na / Si detection intensity ratio at the position of the surface is obtained based on the first regression line.

[0043]

[10] A cover glass comprising the chemically strengthened glass according to any one of [1] to [9].

[0044] According to the present invention, chemically strengthened glass having excellent drop strength can be provided.

[0045] In addition, according to the present invention, a cover glass can also be provided. DETAILED DESCRIPTION

[0046] The chemically strengthened glass of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope of the present invention.

[0047] In this specification, glass compositions are shown as molar percentages based on oxides, and molar % may be abbreviated as %. In addition, “to” indicating a numerical range is used to mean that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0048] "Substantially free" in the glass composition means that it does not contain any impurities other than those inevitably contained in the raw materials, that is, it is not intentionally contained. Specifically, for components other than those described as the glass composition, for example, it is preferably less than 0.1 mol%, more preferably less than 0.08 mol%, and further preferably less than 0.05 mol%.

[0049] The optical waveguide surface stress gauge can accurately measure the stress of the glass in a short time. As an optical waveguide surface stress gauge, there is, for example, FSM-6000 manufactured by Orihara Manufacturing Co., Ltd. However, in principle, the optical waveguide surface stress gauge can only measure stress when the refractive index decreases from the surface of the sample to the inside. In chemically strengthened glass, the layer obtained by replacing the sodium ions inside the glass with external potassium ions can be measured by the optical waveguide surface stress gauge because the refractive index decreases from the surface of the sample to the inside. However, the stress of the layer obtained by replacing the lithium ions inside the glass with external sodium ions cannot be accurately measured by the optical waveguide surface stress gauge.

[0050] The method using a scattered light photoelastic stress meter can measure stress regardless of the refractive index distribution. As a scattered light photoelastic stress meter, for example, there is SLP1000 manufactured by Orihara Manufacturing Co., Ltd. However, the scattered light photoelastic stress meter is sometimes easily affected by surface scattering and cannot accurately measure the stress near the surface.

[0051] For the above reasons, accurate stress measurement can be performed by using the two measuring devices, the optical waveguide surface stress meter and the scattered light photoelastic stress meter, in combination.

[0052] The chemically strengthened glass of the present invention includes a first embodiment, a second embodiment, and a third embodiment described below.

[0053] Hereinafter, each embodiment will be described.

[0054] <Chemically strengthened glass (first embodiment)>

[0055] A first embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, wherein the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (I).

[0056] Formula (I) R Na / Si_100 -R Na / Si_C ≥0.055

[0057] In formula (I), R Na / Si_100 It is the average value of the ratio of the detection intensity of Na distribution to the detection intensity of Si distribution within the range of 91 to 110 μm from one surface of the chemically strengthened glass, when the distance in the thickness direction of the chemically strengthened glass is defined as the depth. It should be noted that the ratio of the detection intensity of Na distribution to the detection intensity of Si distribution is also referred to as "Na / Si detection intensity ratio" hereinafter.

[0058] In formula (I), R Na / Si_C It is an average value of the Na / Si detection intensity ratio within a range of ±25 μm in depth from the center position of the plate thickness of the chemically strengthened glass.

[0059] The method for obtaining the detection of the above-mentioned Na distribution and Si distribution and the method for calculating the above-mentioned Na / Si detection intensity ratio are described below.

[0060] The relationship satisfying the above formula (I) indicates that the detection intensity of Na in the range of 91 to 110 μm at a depth from one surface of the chemically strengthened glass is relatively high compared to the detection intensity of Na in the range of ±25 μm at a depth from the center of the plate thickness. In other words, it indicates that a relatively larger amount of Na is contained in the range of 91 to 110 μm at a depth from one surface of the chemically strengthened glass compared to the range of ±25 μm at a depth from the center of the plate thickness.

[0061] The mechanism by which the first embodiment of the chemically strengthened glass according to the present invention can provide chemically strengthened glass having excellent drop resistance is not yet clear, but the present inventors speculate as follows.

[0062] Chemically strengthened glass such as the present invention is often formed by a two-step chemical strengthening treatment, for example, replacing Li ions contained in a glass plate with Na ions and further replacing Na ions with K ions. At this time, it is considered that when the relationship of the above formula (I) is satisfied in the chemically strengthened glass, it means that Li ions are fully replaced with Na ions within the above depth range of 91 to 110 μm. That is, it is considered that sufficient compressive stress is generated within the above depth range, and the drop strength is improved.

[0063] Hereinafter, a first embodiment of the chemically strengthened glass of the present invention will be described in detail.

[0064] [Element distribution]

[0065] The above-mentioned Si distribution and Na distribution are obtained by analysis using an electron probe microanalyzer (EPMA).

[0066] In the present invention, the Si distribution and the Na distribution in the plate thickness direction of the chemically strengthened glass are obtained by the following method.

[0067] First, chemically strengthened glass was embedded in a resin, a cross section was made with a plane parallel to the thickness direction of the chemically strengthened glass, and the cross section was mirror-polished to obtain a measurement sample. The surface of the cross section of the chemically strengthened glass of the obtained measurement sample was analyzed by EPMA.

[0068] The analysis by EPMA was performed using JXA-8500F manufactured by JEOL. In the analysis by EPMA, line scanning analysis was performed along the plate thickness direction of the chemically strengthened glass of the measurement sample. The detailed measurement conditions were in accordance with the method described in the following Examples.

[0069] The above measurements provide Na distribution and Si distribution in the thickness direction of the chemically strengthened glass. The horizontal axis of the Si distribution and the Na distribution represents depth (μm) and the vertical axis represents detection intensity (count per second: cps).

[0070] To obtain R in the above formula (I) Na / Si_100 When the detection intensity of Na is measured, first, the ratio of the detection intensity of Na to the detection intensity of Si is calculated based on the obtained Na distribution and Si distribution to prepare a distribution. That is, for the measurement points at each depth of each distribution, the value obtained by dividing the value of the detection intensity in the Na distribution by the value of the detection intensity in the Si distribution (Na / Si detection intensity ratio) is calculated, and the distribution of the Na / Si detection intensity ratio is prepared with the horizontal axis representing the depth and the vertical axis representing the Na / Si detection intensity ratio.

[0071] Next, based on the distribution of the Na / Si detection intensity ratio, the arithmetic mean value of the Na / Si detection intensity ratio within the range of 91 to 110 μm from the surface of the chemically strengthened glass was calculated as R Na / Si_100 .

[0072] In the above formula (I), R Na / Si_C The arithmetic mean value of the Na / Si detection intensity ratio within the range of ±25 μm from the center of the plate thickness was calculated based on the distribution of the Na / Si detection intensity ratio obtained by the above method and was taken as R. Na / Si_C .

[0073] It should be noted that the center position of the plate thickness is obtained by measuring the plate thickness using an observation image obtained using a scanning electron microscope attached to EPMA, and half of the depth is used as the center position of the plate thickness. When measuring the plate thickness to obtain the plate thickness, the plate thickness at any five points in the observation image is measured, and the arithmetic average thereof is used as the plate thickness.

[0074] [Formula (I)]

[0075] As described above, the first embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, and the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis satisfy the relationship of the following formula (I).

[0076] Formula (I) R Na / Si_100 -R Na / Si_C ≥0.055

[0077] The above formula (I) defines the Na / Si detection intensity ratio within the range of 91 to 110 μm from the surface. The value on the left side of the above formula (I) is considered to correspond to the compressive stress within the range of 91 to 110 μm from the surface, and is considered to be related to the strength of the stress generated when the chemically strengthened glass is resisted from colliding with other objects. If the above formula (I) is satisfied, excellent drop strength can be obtained. When a greater strength against collision is required, it is preferred to adjust the value on the left side of the above formula (I) to be larger.

[0078] For example, from the viewpoint that the strength of chemically strengthened glass against collision is likely to be increased, it is preferable to satisfy the relationship of the following formula (I-1), and it is more preferable to satisfy the relationship of the following formula (I-2).

[0079] Formula (I-1) R Na / Si_100 -R Na / Si_C ≥0.080

[0080] Formula (I-2) R Na / Si_100 -R Na / Si_C ≥0.100

[0081] Methods for adjusting the parameters of formula (I) are described in detail below.

[0082] [Formula (II)]

[0083] In the first embodiment of the chemically strengthened glass of the present invention, in addition to the above-mentioned formula (I), the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis preferably satisfy the relationship of the following formula (II).

[0084] Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110

[0085] In formula (II), R Na / Si_50 It is the average value of the Na / Si detection intensity ratio within the range of 41 to 60 μm in depth from the surface.

[0086] It should be noted that R Na / Si_50The distribution of the Na / Si detection intensity ratio is obtained by the above-mentioned steps, and the arithmetic mean value of the Na / Si detection intensity ratio in the range of depth 41 to 60 μm is calculated.

[0087] In formula (II), R Na / Si_C and R in the above formula (I) Na / Si_C The meanings are the same, so the description is omitted.

[0088] The above formula (II) defines the Na / Si detection intensity ratio within a depth range of 41 to 60 μm from the surface. The value on the left side of the above formula (II) is considered to correspond to the compressive stress within a depth range of 41 to 60 μm from the surface, and is considered to be related to the strength of the stress generated when the chemically strengthened glass is resisted from colliding with other objects. When a greater strength against collision is required, it is preferred to adjust the value on the left side of the above formula (II) to be larger.

[0089] For example, from the viewpoint that the strength of chemically strengthened glass against collision is likely to be increased, it is preferable to satisfy the relationship of the following formula (II-1), and it is more preferable to satisfy the relationship of the following formula (II-2).

[0090] Formula (II-1) R Na / Si_50 -R Na / Si_C ≥0.115

[0091] Formula (II-2) R Na / Si_50 -R Na / Si_C ≥0.120

[0092] Methods for adjusting the parameters of formula (II) are described in detail below.

[0093] [Formula (III)]

[0094] In the first embodiment of the chemically strengthened glass of the present invention, in addition to the above-mentioned formula (I), the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis preferably satisfy the relationship of the following formula (III).

[0095] Formula (III) R Na / Si_100_0 -R Na / Si_C ≥0.155

[0096] In formula (III), R Na / Si_100_0 In the distribution of the Na / Si detection intensity ratio, a first regression line is prepared from a range of 91 to 110 μm in depth from the surface, and the value of the Na / Si detection intensity ratio at the surface is obtained based on the first regression line.

[0097] In formula (III), R Na / Si_C and R in the above formula (I) Na / Si_CThe meanings are the same, so the description is omitted.

[0098] The distribution of Na / Si detection intensity ratio is obtained through the above steps.

[0099] The first regression line and the second regression line are prepared by determining coefficients using the least square method based on the values ​​of each measurement plot of the distribution of the Na / Si detection intensity ratio, assuming linear regression.

[0100] R Na / Si_100_0 This corresponds to the Na / Si detection intensity ratio of the surface (depth 0 μm) of the chemically strengthened glass obtained by extrapolation from the range of depth 91 to 110 μm.

[0101] The above formula (III) defines a value related to the Na / Si detection intensity ratio within a depth range of 91 to 110 μm from the surface. The value on the left side of the above formula (III) is considered to be related to the compressive stress within a depth range of 91 to 110 μm from the surface, and is considered to be related to the strength of the stress generated when the chemically strengthened glass is resisted from colliding with other objects. When a greater strength against collision is required, it is preferred to adjust the value on the left side of the above formula (III) to be larger.

[0102] For example, from the viewpoint that the strength of chemically strengthened glass against collision is likely to be increased, it is preferable to satisfy the relationship of the following formula (III-1), and it is more preferable to satisfy the relationship of the following formula (III-2).

[0103] Formula (III-1) R Na / Si_100_0 -R Na / Si_C ≥0.160

[0104] Formula (III-2) R Na / Si_100_0 -R Na / Si_C ≥0.190

[0105] Methods for adjusting the parameters of formula (III) are described in detail below.

[0106] In the first embodiment of the chemically strengthened glass of the present invention, the relationship of the above formula (I) only needs to be satisfied within a range of 91 to 110 μm at a depth from one surface of the chemically strengthened glass, but it is preferred that the relationship of the above formula (I) is also satisfied within a range of 91 to 110 μm at a depth from the other surface.

[0107] Similarly, the above formula (II) and the above formula (III) preferably satisfy the above relationship between the above one surface and the other surface.

[0108] [Relationship of Na / Si detection intensity ratio]

[0109] In the first embodiment of the chemically strengthened glass of the present invention, it is preferred that the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis further satisfy the relationship of the following formula (IV).

[0110] Formula (IV) R Na / Si_50_0 -R Na / Si_C ≥0.140

[0111] In formula (IV), R Na / Si_50_0 In the distribution of the Na / Si detection intensity ratio, a first regression line is prepared from the range of 41 to 60 μm in depth from the surface, and the value of the Na / Si detection intensity ratio at the surface position is obtained based on the first regression line.

[0112] In formula (IV), R Na / Si_C and R in the above formula (I) Na / Si_C The meanings are the same, so the description is omitted.

[0113] The distribution of Na / Si detection intensity ratio is obtained through the above steps.

[0114] The first regression line and the second regression line are prepared by determining coefficients using the least square method based on the values ​​of each measurement plot of the distribution of the Na / Si detection intensity ratio, assuming linear regression.

[0115] R Na / Si_50_0 This corresponds to the Na / Si detection intensity ratio on the surface of the chemically strengthened glass obtained by extrapolating from a range of a depth of 41 to 60 μm.

[0116] The above formula (IV) defines a value related to the Na / Si detection intensity ratio within a depth range of 41 to 60 μm from the surface. The value on the left side of the above formula (IV) is considered to be related to the compressive stress within a depth range of 41 to 60 μm from the surface, and is considered to be related to the strength of the stress generated when the chemically strengthened glass is resisted from colliding with other objects. When a greater strength against collision is required, it is preferred to adjust the value on the left side of the above formula (IV) to be larger.

[0117] In the first embodiment of the chemically strengthened glass of the present invention, it is preferred that the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis further satisfy the relationship of the following formula (V).

[0118] Formula (V)R Na / Si_35 -R Na / Si_C ≥0.125

[0119] In formula (V), R Na / Si_35 It is the average value of the Na / Si detection intensity ratio within the range of 31 to 40 μm in depth from the surface.

[0120] It should be noted that R Na / Si_35 The distribution of the Na / Si detection intensity ratio is obtained by the above-mentioned steps, and the arithmetic mean value of the Na / Si detection intensity ratio in the range of depth 31 to 40 μm is calculated.

[0121] In formula (V), R Na / Si_C and R in the above formula (I) Na / Si_C The meanings are the same, so the description is omitted.

[0122] [Relationship of K / Si detection intensity ratio]

[0123] Furthermore, the K distribution and Si distribution in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis preferably satisfy the relationship of the following formula (VI).

[0124] Formula (VI) R K / Si_2_0 -R K / Si_C ≤0.310

[0125] In formula (VI), R K / Si_2_0 In the distribution of the ratio of the detection intensity of the above-mentioned K distribution to the detection intensity of the above-mentioned Si distribution, that is, the K / Si detection intensity ratio, a second regression line is made from the range of 1 to 3 μm at a depth from the above-mentioned surface, and the value of the above-mentioned K / Si detection intensity ratio at the position of the above-mentioned surface is calculated based on the above-mentioned second regression line.

[0126] In formula (VI), R K / Si_C It is an average value of the K / Si detection intensity ratio within a range of depth ±25 μm from the center position of the plate thickness of the chemically strengthened glass.

[0127] In addition, the method of obtaining K distribution by EPMA is the same as the method of obtaining Si distribution and Na distribution.

[0128] The above formula (VI) defines a value related to the K / Si detection intensity ratio within a depth range of 1 to 3 μm from the surface. It is believed that the value on the left side of the above formula (VI) is related to the compressive stress within a depth range of 1 to 3 μm from the surface, and it is believed that the smaller the value on the left side of the formula (VI), the less the K content within a depth range of 1 to 3 μm from the surface. When the K content within a depth range of 1 to 3 μm from the surface is small, it is easy to satisfy the relationships of the above formulas (II), (III) and (IV), and it is easier to increase the strength of the chemically strengthened glass against collisions.

[0129] [composition]

[0130] A first embodiment of the chemically strengthened glass of the present invention is obtained by subjecting a plate glass before chemical strengthening to a chemical strengthening treatment.

[0131] Hereinafter, a preferred composition of the sheet glass before chemical strengthening (hereinafter also referred to as "composition before chemical strengthening") is described. It should be noted that the composition of the sheet glass before chemical strengthening is consistent with the composition at the center of the sheet thickness of the chemically strengthened glass.

[0132] The composition before chemical strengthening is expressed as a molar percentage based on oxides and contains:

[0133] 55-75% SiO2, 8-20% Al2O3, 3-15% Li2O, 1-5% Na2O, 0-3% K2O, 0-10% MgO, 0-3% Y2O3, 0-3% ZrO2, 0-10% CaO, 0-5% SrO, 0-5% ZnO, 0-3% TiO2, 0-1% SnO2, 0-5% P2O5, 0-10% B2O3,

[0134] The ratio of the content of ZrO2 to the total content of Y2O3 and ZrO2 is 0.0 to 0.7.

[0135] The total content of Y2O3 and the content of ZrO2 is greater than 0.0% and less than 3.0%.

[0136] If the amount of material charged is known when manufacturing the flat glass, the composition before chemical strengthening can be calculated from the amount of material charged. In addition, the composition before chemical strengthening can be obtained by calculating the content of each element at the center of the thickness of the chemically strengthened glass. The content of each element at the center of the thickness of the chemically strengthened glass can be measured, for example, by EPMA. The content of Li can be measured by glow discharge emission spectroscopy.

[0137] Hereinafter, each component contained in the composition before chemical strengthening will be described. It should be noted that, for example, the content of SiO2 expressed as a molar percentage based on an oxide may be described as "[SiO2]" below.

[0138] SiO2 is a component that forms a network of glass. It is also a component that improves chemical durability and reduces the occurrence of cracks when the glass surface is damaged.

[0139] In order to improve chemical durability, the content of SiO2 is more preferably 60.0% or more, further preferably 62.0% or more, particularly preferably 64.0% or more, and most preferably 66.0% or more. On the other hand, from the viewpoint of making the meltability good, the content of SiO2 is more preferably 70.0% or less, further preferably 68.0% or less, particularly preferably 67.0% or less, and most preferably 66.0% or less.

[0140] Al2O3 is a component that improves the ion exchange performance during chemical strengthening and increases the surface compressive stress after strengthening.

[0141] From the viewpoint of obtaining the above-mentioned effects, the content of Al2O3 is more preferably 10.0% or more, and further preferably 11.0% or more, 11.5% or more, 12.0% or more, 12.5% ​​or more, and 13.0% or more in the following order. On the other hand, it is sometimes required that the crystal is not easy to grow during melting, devitrification defects are not easy to occur, and the yield is more easily improved, and the high-temperature viscosity of the glass is reduced and it is easy to melt. From the above-mentioned viewpoints, the content of Al2O3 is more preferably 15.0% or less, and further preferably 14.0% or less, 13.5% or less, and 13.0% or less in the following order.

[0142] Both SiO2 and Al2O3 are components that stabilize the structure of glass. In order to reduce brittleness, the total content of SiO2 and Al2O3 is preferably 74.0% or more, more preferably 76.0% or more, and further preferably 78.0% or more.

[0143] In addition, both SiO2 and Al2O3 tend to increase the melting temperature of glass. Therefore, in order to facilitate melting, the total content of SiO2 and Al2O3 is preferably 83.0% or less, more preferably 82.0% or less, further preferably 81.0% or less, and particularly preferably 80.5% or less.

[0144] Li2O is a component that can be ion exchanged and is a component that improves the solubility of glass. By making the glass contain Li2O, the Li ions on the surface of the glass are introduced into the interior of the glass by ion exchange with external Na ions, and the introduced Na ions are further ion exchanged with external K ions. It is easy to obtain a stress distribution with large surface compressive stress and thick compressive stress layer. From the viewpoint of easily obtaining a preferred stress distribution, the content of Li2O is more preferably 8.0% or more, and more preferably 9.0% or more, 9.5% or more, 10.0% or more, 10.2% or more, and 10.4% or more in the following order.

[0145] On the other hand, from the viewpoint that the crystal growth rate during glass molding is low and quality degradation due to devitrification is less likely to occur, the Li2O content is more preferably 14.0% or less, and further preferably 13.5% or less, 13.0% or less, 12.5% ​​or less, 12.0% or less, 11.5% or less, 11.0% or less, and 10.8% or less in the following order.

[0146] Na2O and K2O are components that improve the solubility of glass and reduce the crystal growth rate during glass molding. In order to improve the ion exchange performance, it is also preferable to contain a small amount.

[0147] Na2O is a component that can be ion exchanged in a chemical strengthening treatment using potassium salts, and is a component that reduces the viscosity of glass. In order to obtain the above-mentioned effect, the content of Na2O is preferably 1% or more, and more preferably 1.5% or more, 1.7% or more, 1.9% or more, 2.2% or more, 2.5% or more, 2.8% or more, and 3.0% or more in the following order. On the other hand, from the viewpoint of avoiding a decrease in surface compressive stress (Na_CS) in a strengthening treatment using sodium salts, the content of Na2O is more preferably 4.0% or less, and further preferably 3.0% or less.

[0148] K2O is a component that suppresses devitrification temperature rise and improves ion exchange performance. The content of K2O is more preferably 0.1% or more, further preferably 0.15% or more, particularly preferably 0.2% or more, and most preferably 0.5% or more.

[0149] On the other hand, from the viewpoint of avoiding a decrease in the surface compressive stress (K_CS) during the strengthening treatment with the sodium salt, the content of K2O is more preferably 2.5% or less.

[0150] Expressed as a molar percentage based on oxides, the ratio of the K2O content to the total content of Li2O, Na2O and K2O ([K2O] / ([Li2O]+[Na2O]+[K2O])) is preferably 0.05 to 0.20. From the viewpoint of improving weather resistance, ([K2O] / ([Li2O]+[Na2O]+[K2O])) is preferably 0.05 or more, more preferably 0.07 or more, and further preferably 0.08 or more. On the other hand, from the viewpoint of improving chemical strengthening properties, ([K2O] / ([Li2O]+[Na2O]+[K2O])) is preferably 0.20 or less, more preferably 0.18 or less, and further preferably 0.16 or less.

[0151] From the viewpoint of suppressing the increase in devitrification temperature and reducing the crystal growth rate, it is preferred that all of Li2O, Na2O and K2O are contained. In addition, the sum of the contents of the alkali components represented by [R2O] ([Li2O] + [Na2O] + [K2O]) is preferably 13.0% or more, more preferably 13.5% or more, further preferably 14.0% or more, particularly preferably 14.5% or more, and most preferably 15.0% or more. In addition, from the viewpoint of chemical durability, [R2O] is preferably 18.0% or less, more preferably 17.5% or less, further preferably 17.0% or less, particularly preferably 16.5% or less, and most preferably 16.0% or less.

[0152] In addition, the ratio of the content of K2O to the content of Na2O ([K2O] / [Na2O]) is preferably 0.0 to 1.8. From the viewpoint of more easily obtaining a chemically strengthened glass having excellent drop strength, [K2O] / [Na2O] is preferably 0.3 or more, more preferably 0.5 or more, further preferably 0.6 or more, and particularly preferably 0.75 or more. In addition, from the above viewpoints, [K2O] / [Na2O] is preferably 1.6 or less, more preferably 1.4 or less, and further preferably 1.2 or less.

[0153] The value represented by [Al2O3]-[Na2O]-[K2O]+[Li2O] is preferably 15.0 to 26.0, more preferably 17.0 to 24.0.

[0154] Y2O3 is a component that easily increases the surface compressive stress of chemically strengthened glass and reduces the crystal growth rate. The content of Y2O3 is more preferably greater than 0%, and is further preferably 0.1% or more, 0.2% or more, 0.5% or more, and 1.0% or more in the following order. On the other hand, from the perspective of easily increasing the compressive stress layer during chemical strengthening treatment, the content of Y2O3 is more preferably 2.0% or less.

[0155] ZrO2 is a component that tends to increase the surface compressive stress of chemically strengthened glass. The content of ZrO2 is more preferably greater than 0%, and further preferably in the following order: 0.1% or more, 0.15% or more, 0.2% or more, 0.25% or more, 0.3% or more, and greater than 0.5%.

[0156] On the other hand, from the perspective of suppressing the occurrence of devitrification defects and facilitating increasing the compressive stress value during chemical strengthening treatment, the ZrO2 content is more preferably 2.0% or less, further preferably 1.5% or less, particularly preferably 1.0% or less, and most preferably 0.6% or less.

[0157] From the viewpoint of improving the initial melting property, the total content of ZrO2 and Y2O3 is more preferably 2.4% or less. The lower limit of the total content of ZrO2 and Y2O3 is not particularly limited, but from the viewpoint of improving the strength of the glass, it is more preferably 0.5% or more, and further preferably 0.7% or more, 1.0% or more, and 1.2% or more in the following order.

[0158] The ratio of the content of ZrO2 to the total content of ZrO2 and Y2O3, [ZrO2] / ([ZrO2]+[Y2O3]), is more preferably 0.10 or more, further preferably 0.20 or more, particularly preferably 0.25 or more, and most preferably 0.30 or more. [ZrO2] / ([ZrO2]+[Y2O3]) is more preferably 0.60 or less, further preferably 0.50 or less, particularly preferably 0.45 or less, and most preferably 0.40 or less.

[0159] It is known that ZrO2 and Y2O3 act as nucleating agents when added alone, but by adding ZrO2 and Y2O3 together, a eutectic of ZrO2 and Y2O3 can be formed, thereby controlling the devitrification temperature, crystal growth rate and crystallization start temperature.

[0160] Furthermore, by setting [ZrO 2 ] / ([ZrO 2 ]+[Y 2 O 3 ]) to be within the above range, diffusion of ions in the glass can be suppressed, thereby suppressing a rise in devitrification temperature and suppressing devitrification.

[0161] By setting [ZrO2] / ([ZrO2]+[Y2O3]) to the above range, the glass is stabilized, and the temperature region where nucleation occurs is separated from the temperature region where crystal growth occurs without overlapping, thereby suppressing the increase in the crystal growth rate, thereby suppressing the generation of defects. In addition, by setting [ZrO2] / ([ZrO2]+[Y2O3]) to the above range, the temperature region where nucleation occurs is moved to the low temperature side, thereby suppressing the decrease in the crystallization start temperature, and the manufacturing characteristics can be improved.

[0162] From the viewpoint of suppressing nucleation, the value represented by -25×[ZrO2]+100×[Y2O3] is preferably 135 or less, and more preferably 133 or less, 130 or less, 125 or less, 120 or less, 115 or less, and 110 or less in the following order. The lower limit of the value represented by -25×[ZrO2]+100×[Y2O3] is not particularly limited, but from the viewpoint of suppressing the precipitation of ZrO2-based defects in glass manufacturing, it is preferably 50 or more, more preferably 60 or more, further preferably 70 or more, and particularly preferably 80 or more.

[0163] From the viewpoint of reducing defects in the glass, the value represented by 100×[ZrO2]+63×[Y2O3] is preferably 180 or less, more preferably 175 or less, further preferably 170 or less, particularly preferably 165 or less, and most preferably 160 or less. The lower limit of the value represented by 100×[ZrO2]+63×[Y2O3] is not particularly limited, but from the viewpoint of promoting nucleation, it is preferably 100 or more, more preferably 110 or more, further preferably 125 or more, and particularly preferably 130 or more.

[0164] MgO may be contained in order to reduce viscosity during melting, etc. The MgO content is more preferably 0.05% or more, and further preferably 0.1% or more, 0.2% or more, 0.9% or more, more than 0.9%, and 1.0% or more in the following order.

[0165] On the other hand, from the viewpoint of easily increasing the compressive stress layer during chemical strengthening treatment, the MgO content is more preferably 8.0% or less, and further preferably 7.5% or less, 5.0% or less, 4.0% or less, 3.8% or less, 3.0% or less, 2.0% or less, and 1.5% or less in the following order. By making the MgO content 4.0% or less, acid resistance can be improved.

[0166] In addition, by containing MgO, the phase transition from the β-quartz solid solution to the β-spodumene can be suppressed, and the precipitation of the β-spodumene crystals can be suppressed. Therefore, in Embodiment 2, MgO is preferably contained. From the above viewpoint, it is preferred to contain MgO greater than 0.9% and less than 7.0%. A further preferred range is as described above.

[0167] CaO is a component that improves the meltability of glass and may be contained. The content of CaO is more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.5% or more. On the other hand, from the viewpoint of easily increasing the compressive stress value during chemical strengthening treatment, the content of CaO is more preferably 2.0% or less, further preferably 1.5% or less, particularly preferably 1.0% or less, and most preferably 0.8% or less.

[0168] In order to improve the stability of the glass, it is more preferable to contain at least one of MgO and CaO, and it is further preferable to contain MgO. The total content of MgO and CaO is preferably greater than 0.1%, more preferably 0.5% or more, and further preferably 2.0% or more. From the viewpoint of further improving the chemical strengthening characteristics, the total content of MgO and CaO is preferably 20.0% or less, and more preferably 15.0% or less, 10.0% or less, and 8.0% or less in the following order.

[0169] SrO is a component that improves the solubility of glass. The SrO content is more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.5% or more.

[0170] From the viewpoint of easily increasing the compressive stress value during chemical strengthening treatment, the SrO content is more preferably 3.0% or less, further preferably 2.0% or less, particularly preferably 1.0% or less, and most preferably 0.5% or less.

[0171] BaO is a component that improves the solubility of glass and may be contained. When BaO is contained, the content is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more.

[0172] From the viewpoint of easily increasing the compressive stress value during chemical strengthening treatment, the BaO content is preferably 3.0% or less, more preferably 2.0% or less, further preferably 1.0% or less, and particularly preferably 0.5% or less.

[0173] ZnO is a component that improves the solubility of glass. The content of ZnO is more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.5% or more.

[0174] From the viewpoint of easily increasing the compressive stress value during chemical strengthening treatment, the ZnO content is more preferably 3.0% or less, further preferably 2.0% or less, particularly preferably 1.0% or less, and most preferably 0.5% or less.

[0175] InW is a parameter indicating the degree of mixing of oxides calculated from the contents of alkali metal oxides, alkaline earth metal oxides, and zinc oxide contained in glass. InW is represented by the following formula.

[0176] lnW=ln(([Li2O]+[Na2O]+[K2O]+[MgO]+[CaO]+

[0177] [SrO]+[BaO]+[ZnO])! / ([Li2O]! ×[Na2O]! ×[K2O]! ×[MgO]! ×[CaO]! ×[SrO]! ×[BaO]!

[0178] In formula (1), [Li2O], [Na2O], [K2O], [MgO], [CaO], [SrO], [BaO] and [ZnO] respectively represent the contents of each component of Li2O, Na2O, K2O, MgO, CaO, SrO, BaO and ZnO expressed as molar percentage based on oxides.

[0179] In addition, ! means factorializing a positive number. For example, [XO]! means factorializing a positive number by rounding off the decimal point of the content of the component XO expressed as a molar percentage based on oxide. For example, when Na2O is 4.8 mol%, the factorial of "4" is calculated, that is, 4×3×2×1.

[0180] If the value of lnW is large, the mixing degree of the above-mentioned metal oxides is high, so the devitrification of the glass can be suppressed. From the above viewpoints, lnW is preferably 10 or more, more preferably 12 or more, further preferably 13 or more, and particularly preferably 14 or more. lnW is preferably 20 or less, more preferably 18 or less, and further preferably 17 or less.

[0181] La2O3 is not essential and may be contained for the same reason as Y2O3. La2O3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 0.8% or more. On the other hand, if it is too much, it is difficult to increase the compressive stress layer during chemical strengthening treatment, so La2O3 is preferably 5.0% or less, more preferably 3.0% or less, further preferably 2.0% or less, and particularly preferably 1.5% or less.

[0182] TiO2 is a component that has a high effect of suppressing solarization of glass and can be contained. When TiO2 is contained, the content is preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, particularly preferably 0.05% or more, and most preferably 0.06% or more.

[0183] On the other hand, from the viewpoint of preventing devitrification from occurring and thereby reducing the quality of the chemically strengthened glass, the TiO 2 content is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.25% or less.

[0184] B2O3 reduces the brittleness of glass and improves crack resistance or improves the solubility of glass. The content of B2O3 is more preferably 0.5% or more, further preferably 1.0% or more, and particularly preferably 2.0% or more.

[0185] On the other hand, from the viewpoint of maintaining good acid resistance, the content of B2O3 is preferably 10% or less. The content of B2O3 is more preferably 6.0% or less, further preferably 4.0% or less, and particularly preferably 2.0% or less. From the viewpoint of preventing streaks during melting, it is also preferably substantially free of B2O3.

[0186] P2O5 increases the compressive stress layer during chemical strengthening. The content of P2O5 is more preferably 0.5% or more, further preferably 1.0% or more, and particularly preferably 2.0% or more.

[0187] On the other hand, from the viewpoint of improving acid resistance, the content of P2O5 is more preferably 4.0% or less, and further preferably 2.0% or less. From the viewpoint of preventing streaks during melting, it is also preferred that substantially no P2O5 is contained.

[0188] Nb2O5, Ta2O5, Gd2O3, and CeO2 are components that have the effect of suppressing the discoloration of glass due to exposure and improving the melting property, and can be contained. When these components are contained, the content of each component is preferably 0.03% or more, more preferably 0.1% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and most preferably 1.0% or more. On the other hand, it is preferably 3.0% or less, more preferably 2.0% or less, and further preferably 1.0% or less.

[0189] Fe2O3 has the effect of improving the solubility of glass by absorbing thermal radiation, and is preferably contained when a large melting furnace is used to mass produce glass. The content at this time is expressed as % by weight based on the oxide, preferably 0.002% or more, more preferably 0.005% or more, further preferably 0.007% or more, and particularly preferably 0.01% or more. On the other hand, if the content contains Fe2O3, coloring occurs. From the viewpoint of improving the transparency of the glass, its content is expressed as % by weight based on the oxide, preferably 0.3% or less, more preferably 0.04% or less, further preferably 0.025% or less, and particularly preferably 0.015% or less.

[0190] In addition, other coloring components may be added within the range that does not hinder the realization of the desired chemical strengthening characteristics. As other coloring components, for example, Co3O4, MnO2, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, Nd2O3, etc. can be cited as preferred coloring components.

[0191] As a clarifier during glass melting, SO3, chloride, fluoride, etc. may be appropriately contained. Preferably, As2O3 is not contained. When Sb2O3 is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably, it is not contained.

[0192] From the viewpoint of bubbles in the clarified glass, the content of SnO2 is more preferably 0.1% or more, further preferably 0.2% or more, and particularly preferably 0.3% or more. In addition, in order to suppress the generation of defects, the content of SnO2 is preferably 1% or less, more preferably 0.8% or less, further preferably 0.7% or less, and particularly preferably 0.5% or less.

[0193] (Devitrification temperature)

[0194] The devitrification temperature of the glass before chemical strengthening is preferably 1300° C. or lower. The devitrification temperature is more preferably 1280° C. or lower, and further preferably 1250° C. or lower. It is particularly preferably 1240° C. or lower, 1230° C. or lower, 1220° C. or lower, and 1210° C. or lower in the following order. The lower limit of the devitrification temperature is not particularly limited, but is usually 1100° C. or higher.

[0195] By setting the devitrification temperature to 1300°C or less (preferably 1250°C or less), the glass can be stably molded and the manufacturing characteristics can be improved. Specifically, for example, when forming glass by the float process, if crystals are generated before the molten glass flows into the float bath, the crystals may corrode the bricks constituting the float bath. By setting the devitrification temperature to 1300°C or less (preferably 1250°C or less), the erosion of the bricks can be suppressed.

[0196] It should be noted that the devitrification temperature of glass refers to the minimum temperature at which no crystals are precipitated on the surface or inside of the glass after placing crushed glass particles of 2 mm to 3 mm in a platinum dish and heat treating them in an electric furnace controlled at a constant temperature for 17 hours, and observing them under an optical microscope after the heat treatment.

[0197] (Glass transition temperature Tg, crystallization start temperature Tcs, crystallization peak temperature Tc)

[0198] In this specification, the measurement using a differential scanning calorimeter (DSC) is performed as follows: glass is crushed in an agate mortar, and about 70 mg of a powder having a uniform particle size of 106 to 180 μm is heated from room temperature to 1200° C. at a heating rate of 10° C. / min.

[0199] For glass before chemical strengthening, the crystallization start temperature Tcs measured by DSC is preferably 790° C. or higher, more preferably 800° C. or higher, further preferably 810° C. or higher, further preferably 815° C. or higher, particularly preferably 820° C. or higher, and most preferably 825° C. or higher. The upper limit of the crystallization start temperature is not particularly limited, but is usually 900° C. or lower.

[0200] By setting the crystallization start temperature Tcs to be above 790°C, manufacturing characteristics can be improved. Specifically, for example, in the molding of a three-dimensional shape (for example, 2.5D or 3D molding. Hereinafter, it is also referred to as three-dimensional molding) in which the glass is formed into a plate and then heat-treated, the temperature rises from room temperature to the molding temperature and passes through the nucleation temperature, which easily causes defects caused by crystallization. By setting the crystallization start temperature Tcs to be above 790°C, molding can be performed without passing through the nucleation temperature when the temperature rises from room temperature to the molding temperature, and the generation of defects can be suppressed.

[0201] The glass transition temperature Tg in this specification is the intersection point of the curve obtained by DSC and the auxiliary line. The crystallization start temperature Tcs of glass in this specification refers to the temperature of the peak top when the glass is heated at 10°C / min using DSC.

[0202] The ratio of the crystallization start temperature Tcs of the glass before chemical strengthening to the glass transition temperature Tg (Tcs+273.15) / (Tg+273.15) is preferably 1.10 or more, more preferably 1.15 or more, further preferably 1.20 or more, and particularly preferably 1.25 or more. By making (Tcs+273.15) / (Tg+273.15) 1.10 or more, the generation of defects in three-dimensional molding can be suppressed and the molding characteristics can be improved. The upper limit of (Tcs+273.15) / (Tg+273.15) is not particularly limited, but is generally preferably 1.6 or less from the viewpoint of the moldability of the glass. In addition, the unit of Tcs and Tg in "(Tcs+273.15) / (Tg+273.15)" is "°C", and "(Tcs+273.15) / (Tg+273.15)" is the same as "Tcs / Tg" when the unit is "K".

[0203] The value (Tcs-Tg) obtained by subtracting the glass transition temperature Tg from the crystallization start temperature Tcs of the glass before chemical strengthening is preferably 180°C or more, more preferably 200°C or more. It is further preferably 210°C or more, further preferably 215°C or more, particularly preferably 225°C or more, and most preferably 230°C or more. By setting (Tcs-Tg) to 200°C or more, the generation of defects in three-dimensional molding can be suppressed and the molding characteristics can be improved. The upper limit of (Tcs-Tg) is not particularly limited, but is generally preferably 400°C or less from the viewpoint of the moldability of the glass.

[0204] The value obtained by subtracting the glass transition temperature Tg from the crystallization start temperature Tcs of the glass before chemical strengthening (Tcs-Tg) is preferably 180°C or higher, more preferably 185°C or higher.

[0205] From the viewpoint of reducing warpage after chemical strengthening, the glass transition temperature Tg is preferably 500° C. or higher, more preferably 520° C. or higher, and further preferably 540° C. or higher. From the viewpoint of facilitating float molding, it is preferably 750° C. or lower, more preferably 700° C. or lower, further preferably 650° C. or lower, particularly preferably 600° C. or lower, and most preferably 580° C. or lower.

[0206] The crystallization peak temperature Tc of the glass before chemical strengthening is preferably 790°C or more, more preferably 800°C or more, and further preferably 810°C or more. By setting the crystallization peak temperature Tc to 790°C or more, stable molding is possible. Most preferably, no crystallization peak is observed. The upper limit of the crystallization peak temperature Tc is not particularly limited, but is usually 950°C or less.

[0207] (Crystal Growth Rate)

[0208] The glass before chemical strengthening contains MgO, which can inhibit the phase transition of the crystal phase from the β-quartz solid solution to the β-spodumene, and can inhibit the precipitation of the β-spodumene crystal. Therefore, even if the glass before chemical strengthening is kept at 1000°C for 30 minutes, the precipitation of β-spodumene can be inhibited. In addition, the crystal growth rate can be further reduced.

[0209] When the glass before chemical strengthening contains MgO, only β-quartz solid solution is the first precipitation phase, and the crystal growth rate of β-quartz solid solution at 1000°C is preferably 4000 μm / hr or less, more preferably 3800 μm / hr or less, further preferably 3500 μm / hr or less, particularly preferably 3200 μm / hr or less, and most preferably 2700 μm / hr or less.

[0210] If crystallization occurs in the glass during the glass forming process, defects will occur. For example, when forming by float process, since the crystallization in the float tank starts from a high temperature and is cooled, defects will occur where the temperature region where nucleation occurs overlaps with the temperature region where crystal growth occurs.

[0211] In ordinary glass, the temperature region where nucleation occurs does not overlap with the temperature region where crystal growth occurs, but in glass containing a large amount of Al2O3 and Li2O, there is a tendency that the temperature region where nucleation occurs overlaps with the temperature region where crystal growth occurs at around 1000°C. Here, even if the nucleation and crystal growth rates overlap, it will not become a defect as long as the crystal growth rate is slow. Therefore, by making the crystal growth rate of the β-quartz solid solution at 1000°C less than 600μm / hr, crystallization in the molding process can be suppressed.

[0212] In this specification, the crystal growth rate of β-quartz solid solution at 1000°C is obtained by keeping a glass sample at 1000°C for 30 minutes, measuring the length of crystals in the glass with a polarizing microscope, and calculating the average value. In addition, the crystal growth rate of β-spodumene at 1000°C is also obtained by the same method.

[0213] The “β-OH value” is a value obtained by measuring the reference wavelength of 4000 cm by FT-IR. -1 The transmittance at X1 (%), the absorption wavelength of hydroxyl group is 3570cm -1 The minimum transmittance X2 (%) in the vicinity and the thickness t (unit: mm) of the glass plate are calculated according to the formula (1).

[0214] β-OH value = (1 / t)log 10 (X1 / X2)·····(1)

[0215] In addition, the β-OH value can be adjusted by the amount of water contained in the glass raw material and the dissolution conditions.

[0216] The β-OH value of the glass before chemical strengthening is preferably 0.1 mm -1 More preferably 0.15 mm -1 More preferably, 0.2 mm -1 Above, particularly preferably 0.22 mm -1 Above, most preferably 0.25mm -1 above.

[0217] The β-OH value is an indicator of the amount of water in the glass. Glass with a large β-OH value tends to have a low softening point and is easy to bend. On the other hand, from the perspective of improving the strength of glass by chemical strengthening, if the β-OH value of the glass becomes larger, the surface compressive stress (CS) value after chemical strengthening tends to become smaller. From the above perspectives, the β-OH value is preferably 0.5 mm -1 Below, more preferably 0.4 mm -1 Below, more preferably 0.3 mm -1 the following.

[0218] In the preferred embodiment described later, the glass before chemical strengthening is subjected to the first-stage chemical strengthening with a Na salt and then subjected to the second-stage chemical strengthening with a Li-K mixed salt, from the viewpoint that K is easily introduced into the glass, and the drop strength of the glass after chemical strengthening is easily improved, the ratio of Na_DOL to K_DOL defined below, i.e., Na_DOL / K_DOL, is preferably 26 or less, more preferably 25 or less, 24 or less, 23 or less, 22 or less, 21 or less, and 20 or less in the following order.

[0219] In addition, from the perspective of avoiding excessive incorporation of K into the glass and preventing glass breakage when performing the second stage of chemical strengthening with a Li-K mixed salt after the first stage of chemical strengthening with a Na salt, Na_DOL / K_DOL is preferably greater than 15, and more preferably greater than 16, greater than 16.5, greater than 17, greater than 17.5, and greater than 18 in the following order.

[0220] K_DOL: Depth of compressive stress layer of chemically strengthened glass in which ion exchange was performed using a molten salt composed of 100% potassium nitrate

[0221] Na_DOL: Depth of compressive stress layer of chemically strengthened glass in which ion exchange is performed using molten salt composed of 100% sodium nitrate

[0222] Here, the time and temperature of ion exchange in the calculation of the above K_DOL and the above Na_DOL are the same conditions.

[0223] From the viewpoint of improving impact resistance, the fracture toughness value K1c of the glass before chemical strengthening is preferably 0.800 MPa·m 1 / 2 More preferably, 0.810 MPa·m 1 / 2 More preferably, it is 0.820 MPa·m 1 / 2 Above, particularly preferably 0.830 MPa·m 1 / 2 Above, the most preferred is 0.840 MPa·m 1 / 2 The upper limit of the fracture toughness value of the glass of the present invention is not particularly limited, but is typically 1.0 MPa·m 1 / 2 the following.

[0224] When the glass before chemical strengthening is a plate-shaped glass plate, from the viewpoint of improving the effect of chemical strengthening, the plate thickness (t) is, for example, preferably 2 mm or less, more preferably 1.5 mm or less, further preferably 1 mm or less, further preferably 0.9 mm or less, particularly preferably 0.8 mm or less, and most preferably 0.7 mm or less. In addition, from the viewpoint of obtaining a sufficient strength improvement effect by chemical strengthening treatment, the plate thickness is, for example, preferably 0.4 mm or more, more preferably 0.5 mm or more.

[0225] The shape of the glass before chemical strengthening may be a shape other than a plate shape depending on the product to which it is applied, the purpose, etc. In addition, the glass plate may have a border shape with different thicknesses on the outer periphery. In addition, the shape of the glass plate is not limited to this, for example, the two main surfaces may not be parallel to each other, and all or part of one or both of the two main surfaces may be a curved surface. More specifically, the glass plate may be, for example, a flat glass plate without warping, and may also be a curved glass plate with a curved surface.

[0226] (Manufacturing method)

[0227] Glass before chemical strengthening can be manufactured by a common method. For example, the raw materials of each component of the glass are mixed and heated and melted in a glass melting furnace. Thereafter, the glass is homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.

[0228] As the forming method of the glass sheet, for example, the float process, the press process, the fusion process and the down-draw process can be cited. The float process suitable for mass production is particularly preferred. In addition, continuous forming methods other than the float process, for example, the fusion process and the down-draw process are also preferred.

[0229] Thereafter, the formed glass is ground and polished as required to form a glass substrate. It should be noted that when cutting or chamfering the glass substrate to a predetermined shape and size, it is preferred to cut or chamfer the glass substrate before performing the chemical strengthening treatment described later, because a compressive stress layer is also formed on the end surface by the subsequent chemical strengthening treatment.

[0230] [Chemical strengthening treatment]

[0231] A first embodiment of the chemically strengthened glass of the present invention is obtained by subjecting a glass plate before chemical strengthening to a chemical strengthening treatment.

[0232] The chemical strengthening treatment can be performed by a known method. The chemical strengthening treatment is performed, for example, by contacting a molten salt of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius (typically a K ion) with a glass plate. The contact of the glass plate with the molten salt of the metal salt is performed, for example, by immersing the glass plate in the molten salt of the metal salt.

[0233] Through the contact between the glass plate and the molten salt of the metal salt, the metal ions with a small ionic radius in the glass plate (typically Na ions or Li ions) are replaced by metal ions with a large ionic radius (typically K ions relative to Na ions, and Na ions and K ions relative to Li ions).

[0234] The chemical strengthening treatment, i.e., the ion exchange treatment, is performed, for example, by immersing the glass plate in a molten salt such as potassium nitrate heated to 360 to 600° C. for 0.1 to 500 hours. It should be noted that the heating temperature of the molten salt is preferably 375° C. or higher, and preferably 500° C. or lower. The immersion time of the glass plate in the molten salt is preferably 0.3 hours or more, and preferably 200 hours or less.

[0235] As the metal salt contained in the molten salt for chemical strengthening treatment, nitrates, sulfates, carbonates, chlorides, etc. can be mentioned. Among them, as nitrates, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate and silver nitrate can be mentioned. As sulfates, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate and silver sulfate can be mentioned. As carbonates, lithium carbonate, sodium carbonate and potassium carbonate can be mentioned. As chlorides, lithium chloride, sodium chloride, potassium chloride, cesium chloride and silver chloride can be mentioned. These metal salts can be used alone or in combination.

[0236] The parameters in the above formula (I) etc. can be controlled by the processing conditions of the chemical strengthening treatment. More specifically, the above parameters can be adjusted by the type and composition of the molten salt provided for the chemical strengthening treatment, the temperature of the molten salt, and the contact time with the molten salt. In addition, the above parameters can also be adjusted by the composition of the glass before chemical strengthening provided for the chemical strengthening treatment.

[0237] In addition, in the present embodiment, the chemical strengthening treatment may be performed only once, or may be performed a plurality of times under two or more different conditions (multi-stage strengthening). The chemical strengthening treatment may be performed in one stage, but preferably in two or more stages.

[0238] The chemical strengthening treatment preferably brings the glass before chemical strengthening containing Li into contact with a molten salt of a metal salt containing at least Na ions (first molten salt), and then into contact with a molten salt of a metal salt containing at least K ions (second molten salt).

[0239] The first molten salt also preferably contains a metal salt containing Na ions and a metal salt containing K ions. When the first molten salt contains a metal salt containing Na ions and a metal salt containing K ions, the content of the metal salt containing Na ions is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 40% by mass or more relative to the total mass of the first molten salt. In addition, the first molten salt may be composed only of a metal salt containing Na ions.

[0240] In addition, the second molten salt also preferably contains a metal salt containing K ions and a metal salt containing Li ions. The second molten salt may further contain a metal salt containing Na ions.

[0241] The chemically strengthened glass of the present invention preferably has a surface compressive stress value of 600 MPa or more, more preferably 700 MPa or more, and further preferably 800 MPa or more when the thickness of the glass is 0.7 mm. The depth of the compressive stress layer of the chemically strengthened glass of the present invention is usually preferably 60 μm or more, more preferably 70 μm or more, and further preferably 80 μm or more. If the depth of the compressive stress layer is 60 μm or more, the drop strength can be further improved.

[0242] <Chemically strengthened glass (second embodiment)>

[0243] A second embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, wherein the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (II).

[0244] Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110

[0245] Formula (II) is the same as Formula (II) described in the first embodiment, and therefore description thereof is omitted.

[0246] The relationship satisfying the above formula (II) indicates that the detection intensity of Na in the range of 41 to 60 μm at a depth from one surface of the chemically strengthened glass is relatively higher than the detection intensity of Na in the range of ±25 μm at a depth from the center of the plate thickness. In other words, it indicates that more Na is contained in the range of 41 to 60 μm at a depth from one surface of the chemically strengthened glass than in the range of ±25 μm at a depth from the center of the plate thickness.

[0247] The mechanism by which the second embodiment of the chemically strengthened glass according to the present invention can provide chemically strengthened glass having excellent drop resistance is not yet clear, but the present inventors speculate as follows.

[0248] Chemically strengthened glass such as the present invention is often formed by, for example, replacing Li ions contained in a glass plate with Na ions and further replacing Na ions with K ions in two stages of chemical strengthening treatment. At this time, it is considered that when the relationship of the above formula (II) is satisfied in the chemically strengthened glass, it means that Li ions are fully replaced with Na ions within the above depth range of 41 to 60 μm. That is, it is considered that sufficient compressive stress is generated within the above depth range, and the drop strength is improved.

[0249] The second embodiment of the chemically strengthened glass of the present invention is similar to the preferred embodiment of the first embodiment except that the relationship of the above-mentioned formula (II) is satisfied, and therefore the description thereof will be omitted.

[0250] In addition, in the second embodiment of the chemically strengthened glass of the present invention, it is also preferable to satisfy the relationship of the above formula (I) described in the first embodiment. In addition, it is also preferable to satisfy the relationship of the above formula (I-1) or formula (I-2) described in the first embodiment.

[0251] <Chemically strengthened glass (third embodiment)>

[0252] A third embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, wherein the Na distribution and Si distribution in the plate thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (III).

[0253] Formula (III) R Na / Si_100_0 -R Na / Si_0 ≥0.155

[0254] Formula (III) is the same as Formula (III) described in the first embodiment, and therefore description thereof is omitted.

[0255] The relationship satisfying the above formula (III) indicates that the detection intensity of Na in the range of 91 to 110 μm at a depth from one surface of the chemically strengthened glass is relatively higher than the detection intensity of Na in the range of ±25 μm at a depth from the center of the plate thickness. In other words, it indicates that more Na is contained in the range of 91 to 110 μm at a depth from one surface of the chemically strengthened glass than in the range of ±25 μm at a depth from the center of the plate thickness.

[0256] The mechanism by which the second embodiment of the chemically strengthened glass of the present invention can provide chemically strengthened glass having excellent drop resistance is not clear, but the present inventors speculate as follows.

[0257] Chemically strengthened glass such as the present invention is often formed by, for example, replacing Li ions contained in a glass plate with Na ions and further replacing Na ions with K ions in two stages of chemical strengthening treatment. At this time, it is considered that when the relationship of the above formula (III) is satisfied in the chemically strengthened glass, it means that Li ions are fully replaced with Na ions within the above depth range of 91 to 110 μm. That is, it is considered that sufficient compressive stress is generated within the above depth range, and the drop strength is improved.

[0258] The third embodiment of the chemically strengthened glass of the present invention is similar to the preferred embodiment of the first embodiment except that the relationship of the above-mentioned formula (III) is satisfied, and therefore the description thereof will be omitted.

[0259] In addition, in the third embodiment of the chemically strengthened glass of the present invention, it is also preferable to satisfy the relationship of the above formula (I) described in the first embodiment. In addition, it is also preferable to satisfy the relationship of the above formula (I-1) or formula (I-2) described in the first embodiment.

[0260] <Application>

[0261] The chemically strengthened glass of the present invention (the first embodiment, the second embodiment and the third embodiment) is useful, for example, as a cover glass. In particular, it is useful as a cover glass used in mobile devices such as mobile phones, smart phones, mobile information terminals (PDAs) and tablet terminals. In addition, it is also useful for cover glass of display devices such as televisions (TVs), personal computers (PCs) and touch panels that are not intended to be carried, walls of buildings such as houses or high-rise buildings (full-screen displays), window glass and other building materials, as well as interiors of desktops, cars and airplanes. In addition, it is also useful as a cover glass of the above-mentioned articles. In addition, by bending and bending, it can also be used for purposes such as shells with curved shapes.

[0262] Example

[0263] The present invention will be described in more detail below based on examples.

[0264] The materials, usage amounts, ratios, treatment contents, and treatment procedures shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited to the following examples.

[0265] It should be noted that Examples 1 to 3 are examples, and Examples 4 and 5 are comparative examples.

[0266] <Production of chemically strengthened glass>

[0267] First, glass raw materials were melted in a platinum crucible to produce glass so as to have each glass composition represented by the molar percentage based on the oxides shown in Table 1. In the following Table 1, trace components are sometimes described by external division, with the total content other than the trace components being 100 mol %.

[0268] Specifically, oxides, hydroxides, carbonates, nitrates, and the like used as glass raw materials are appropriately selected from commonly used glass raw materials, and 1000 g of glass is weighed.

[0269] Next, the mixed raw materials are placed in a platinum crucible and put into a resistance-heated electric furnace at 1500-1700°C for melting for about 3 hours, and degassing is performed to make it homogenous to obtain molten glass. The obtained molten glass is poured into the mold material, kept at a temperature of glass transition temperature + 50°C for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block is cut and ground to make flat glass. Both sides of the obtained flat glass are mirror-finished to finally obtain a flat glass with a length of 120mm×width of 60mm×plate thickness of 0.7mm.

[0270] The respective flat glass sheets obtained in the above steps were subjected to chemical strengthening treatment under the conditions described in Table 1, thereby obtaining chemically strengthened glasses of Examples 1 to 5.

[0271] <Measurement and evaluation>

[0272] Using the obtained chemically strengthened glass, a sample for measurement was prepared according to the above-mentioned procedure, and analyzed by EPMA (JXA-8500F manufactured by JEOL) to obtain Na distribution and Si distribution.

[0273] The measurement conditions and the like of EPMA are as follows.

[0274] Spectroscopic crystals: PETJ (K-Kα), TAPH (Na-Kα), PETH (Si-Kα)

[0275] Electron beam acceleration voltage: 15kV

[0276] · Irradiation electron beam current: 30nA

[0277] Cumulative time: 1000msec / point

[0278] ·Measurement point interval: 1μm

[0279] The drop strength of the chemically strengthened glass of each example was evaluated by the following method.

[0280] The chemically strengthened glass of each example is embedded in a structure with a mass and rigidity adjusted to the size of a common smartphone currently used, and a simulated smartphone is made. The simulated smartphone is made to fall freely onto #180 SiC sandpaper while changing the height in such a way that the side provided with the chemically strengthened glass becomes the ground side. The drop height is first dropped from a height of 5 cm. If the chemically strengthened glass does not break after falling from a height of 5 cm, drop it from a height of 10 cm. If the chemically strengthened glass does not break after further falling from a height of 10 cm, drop it from a height of 15 cm. In this way, if it does not break after falling, repeat the operation of dropping from a position 5 cm higher than the previous drop height until the chemically strengthened glass breaks. According to the above steps, the height at which the chemically strengthened glass breaks for the first time is used as the drop height.

[0281] The drop heights were measured for 19 tempered glasses, and the arithmetic mean of the drop heights was taken as the drop height and is shown in the following table.

[0282] It should be noted that a larger drop height value means that the chemically strengthened glass does not break even if dropped from a higher position, that is, it has a greater drop strength.

[0283] <Results>

[0284] The composition of the glass before chemical strengthening subjected to the chemical strengthening treatment in each example, the conditions of the chemical strengthening treatment, the above-mentioned measurement results, and the above-mentioned evaluation results are shown in the following table.

[0285] In addition, in the table, the column "Na / Si distribution" shows the following contents.

[0286] "31-40 μm": the value on the left side of the above formula (V)

[0287] "41-60 μm": the value on the left side of the above formula (II)

[0288] "41-60 μm regression line": the value on the left side of the above formula (IV)

[0289] "91-110 μm": the value on the left side of the above formula (I)

[0290] "Regression line of 91-110 μm": the value on the left side of the above formula (III)

[0291] · "Central part ±25 μm": R in the above formula (I) Na / Si_C Value

[0292] In addition, in the table, the column "K / Si distribution" shows the following contents.

[0293] "Regression line of 1-3 μm": the value on the left side of the above formula (VI)

[0294] · "Central part ±25 μm": R in the above formula (VI) K / Si_C Value

[0295] In the table, the column "#180" in the column "Drop Strength" indicates the drop height when dropped onto #180 SiC sandpaper.

[0296] [Table 1]

[0297]

[0298] The results shown in Table 1 show that Examples 1 to 3 satisfying the requirement of the above formula (I), i.e., having a value of 0.055 or more in the column "91-110 μm", were found to have superior drop strength compared to Examples 4 and 5 not satisfying the requirement of the above formula (I).

[0299] In addition, from the results shown in Table 1, it was confirmed that Examples 1 to 3 satisfying the requirement of the above formula (II), that is, having a value of 0.110 or more in the "41-60 μm" column, had superior drop strength compared with Examples 4 and 5 not satisfying the requirement of the above formula (II).

[0300] According to the results shown in Table 1, Examples 1 to 3 satisfying the requirement of the above formula (III), i.e., having a value of 0.155 or more in the column of "91-110 μm regression curve", have superior drop strength compared with Examples 4 and 5 not satisfying the requirement of the above formula (III).

Claims

1. A chemically strengthened glass, which is a plate-shaped chemically strengthened glass, The Na distribution and Si distribution in the thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (I): Formula (I) R Na / Si_100 -R Na / Si_C ≥0.055 In formula (I), R Na / Si_100 is an average value of the Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution within a range of 91 to 110 μm from one surface of the chemically strengthened glass, when the distance in the thickness direction of the chemically strengthened glass is defined as the depth, In formula (I), R Na / Si_C It is an average value of the Na / Si detection intensity ratio within a range of depth ±25 μm from the center position of the thickness of the chemically strengthened glass.

2. The chemically strengthened glass according to claim 1, wherein: Further satisfying the relationship of the following formula (II), Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110 In formula (II), R Na / Si_50 It is an average value of the Na / Si detection intensity ratio within a range of 41 to 60 μm in depth from the surface.

3. The chemically strengthened glass according to claim 1 or 2, wherein: Further satisfying the relationship of the following formula (III), Formula (III) R Na / Si_100_0 -R Na / Si_C ≥0.155 In formula (III), R Na / Si_100_0 In the distribution of the Na / Si detection intensity ratio, a first regression line is prepared from a range of 91 to 110 μm in depth from the surface, and the value of the Na / Si detection intensity ratio at the surface position is obtained based on the first regression line.

4. The chemically strengthened glass according to claim 1 or 2, wherein: The K distribution and Si distribution in the thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (VI): Formula (VI)R K / Si_2_0 -R K / Si_C ≤0.310 In formula (VI), R K / Si_2_0 In the distribution of the ratio of the detection intensity of the K distribution to the detection intensity of the Si distribution, that is, the K / Si detection intensity ratio, a second regression line is made from a range of 1 to 3 μm in depth from the surface, and the value of the K / Si detection intensity ratio at the position of the surface is obtained based on the second regression line, In formula (VI), R K / Si_C It is an average value of the K / Si detection intensity ratio within a range of depth ±25 μm from the center position of the thickness of the chemically strengthened glass.

5. The chemically strengthened glass according to claim 1 or 2, wherein: The composition at the center of the plate thickness is expressed in terms of molar percentage based on oxides, and contains 55-75% SiO2, 8-20% Al2O3, 3-15% Li2O, 1-5% Na2O, 0-3% K2O, 0-10% MgO, 0-3% Y2O3, 0-3% ZrO2, 0-10% CaO, 0-5% SrO, 0-5% ZnO, 0-3% TiO2, 0-1% SnO2, 0-5% P2O5, and 0-10% B2O3. The ratio of the content of ZrO2 to the total content of Y2O3 and ZrO2 is 0.0 to 0.

7. The total content of Y2O3 and the content of ZrO2 is greater than 0.0% and is less than or equal to 3.0%.

6. The chemically strengthened glass according to claim 1 or 2, wherein: Regarding the composition at the center of the plate thickness, the ratio of the content of K2O to the content of Na2O is 0.0 to 1.

8.

7. The chemically strengthened glass according to claim 1 or 2, wherein: The composition at the center of the plate thickness is 15.0 to 26.0, represented by [Al2O3]-[Na2O]-[K2O]+[Li2O]. Here, [Al2O3], [Na2O], [K2O] and [Li2O] respectively represent the contents of Al2O3, Na2O, K2O and Li2O in molar percentage based on oxides.

8. A chemically strengthened glass, which is a plate-shaped chemically strengthened glass, The Na distribution and Si distribution in the thickness direction of the chemically strengthened glass analyzed by an electron probe microanalyzer satisfy the relationship of the following formula (II): Formula (II) R Na / Si_50 -R Na / Si_C ≥0.110 In formula (II), R Na / Si_50 is an average value of the Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution within a range of 41 to 60 μm from one surface of the chemically strengthened glass, when the distance in the thickness direction of the chemically strengthened glass is defined as the depth, In formula (II), R Na / Si_C It is an average value of the Na / Si detection intensity ratio within a range of depth ±25 μm from the center position of the thickness of the chemically strengthened glass.

9. A chemically strengthened glass, which is a plate-shaped chemically strengthened glass, The Na distribution and Si distribution in the thickness direction of the chemically strengthened glass analyzed by an electron beam microanalyzer satisfy the relationship of the following formula (III): Formula (III) R Na / Si_100_0 -R Na / Si_C ≥0.155 In formula (III), R Na / Si_100_0 When the distance in the thickness direction of the chemically strengthened glass is defined as the depth, in the distribution of the ratio of the detection intensity of the Na distribution to the detection intensity of the Si distribution, that is, the Na / Si detection intensity ratio, a first regression line is prepared from a range of 91 to 110 μm at a depth from the surface, and the value of the Na / Si detection intensity ratio at the position of the surface is obtained based on the first regression line. 10 . A cover glass comprising the chemically strengthened glass according to claim 1 .